Analisis Gangguan Arus Hubung Singkat Trafo Distribusi 48-PT-33-7 Menggunakan ETAP (Studi Kasus Di Perumahan PT. Badak NGL) - Abdul Zain; Rifki Chairul Afwan (Jurnal Teknik Mesin Sinergi, 2019)
The high frequency of short circuit current fault in power grid PT. Badak NGL Bontang in 2017 becomes a serious problem. One of them is the Short Circuit at Distribution Transformer 48-PT-33-7 which resulted in a feeder 48-FDR-33 trip and cut off the power to all connected loads. This research is conducted to know the value of short circuit current fault by manual calculation and compared with the simulation software ETAP 12.6 which made system modeling refers to real network configuration in the field. After that, ETAP conducted simulation and short circuit analysis in transformer 48-PT-33-7. The calculation result is known that the short circuit current value between manual calculation and ETAP simulation is relatively same, ie 553,8 A / 555 A (one phase to ground), 891,47A / 885 A (two phase), 918,16 A / 950 A (two phase to ground), 1029.41 A / 1022 A (three phases). From the simulation also known the coordination sequence of the protection system works properly when the fault occurs. So from these two results indicate that the installed protection system is in accordance with the standard in securing the power grid from short-circuiting current fault.